Rising the Factors of Arabic Language Learning Strategies for Indonesian Second Learners - Febriani, Suci; Husna, Ilya; Ade Mela, Desriliwa (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2024)
This research aims to analyze Arabic language learning strategies and the factors that influence them among foreign learners at UIN Imam Bonjol Padang. The research approach used is a case study with data collection techniques including observation, interviews to 6 foreign learners and documentation, while the data analysis technique used data triangulation techniques. The research results show that the Arabic language learning strategy for foreign learners is media digital, media social, film, telphone, reading materials while the influencing factors are information media-based infrastructure and collaborative peer review by peers. Research findings inform that the integration of the use of eclectic strategies can accelerate the achievement of foreign language learning for non-native speakers. This research is limited in the methods and samples used, so the researcher recommends further research to identify other variables.